Frontispiece: Core Electron Topologies in Chemical Compounds: Case Study of Carbon versus Silicon. Issue 24 (6th June 2018) - Yoshida, Daisuke; Raebiger, Hannes; Shudo, Ken‐ichi; Ohno, Koichi
Abstract : Carbon versus Silicon First‐principles calculation of C2, Si2, and their hydrides X2 H2 n reveal a striking difference in their electronic structures, as shown by D. Yoshida, H. Raebiger et al. in their Communication onpage 7012 ff.